2019
DOI: 10.18632/oncotarget.26748
|View full text |Cite
|
Sign up to set email alerts
|

An immunogenic NSCLC microenvironment is associated with favorable survival in lung adenocarcinoma

Abstract: The tumor microenvironment consists of an intricately organized system through which immune cells and cancer cells may communicate to regulate antitumor immunogenicity. To this end, non-small cell lung cancer (NSCLC) has been shown to activate a variety of immunological mechanisms, thereby broadening our understanding of lung cancer immunobiology. However, while recent work has highlighted the importance of NSCLC immunology and prognosis, studies have not yet examined the tumor microenvironment (TME) globally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 63 publications
4
23
0
Order By: Relevance
“…Besides, the KEGG pathway enrichment displayed that the DEGs mostly clustered in the Cytokine−cytokine receptor interaction, the Chemokine signaling pathway, and the Viral protein interaction with cytokine and cytokine receptor. Consistent with these results, previous studies have shown that the biological processes of the immune system are critical to the formation of a complicated LUAD tumor microenvironment 10,30,[37][38][39] . In the past few years, the understanding of the immunological characteristics of LUAD has increased, and the development of effective LUAD immunotherapy strategies has drawn wide attention [40][41][42][43][44] .…”
Section: Discussionsupporting
confidence: 86%
“…Besides, the KEGG pathway enrichment displayed that the DEGs mostly clustered in the Cytokine−cytokine receptor interaction, the Chemokine signaling pathway, and the Viral protein interaction with cytokine and cytokine receptor. Consistent with these results, previous studies have shown that the biological processes of the immune system are critical to the formation of a complicated LUAD tumor microenvironment 10,30,[37][38][39] . In the past few years, the understanding of the immunological characteristics of LUAD has increased, and the development of effective LUAD immunotherapy strategies has drawn wide attention [40][41][42][43][44] .…”
Section: Discussionsupporting
confidence: 86%
“…Zeng et al provides potential TME-related biomarker for the therapy and prognosis of RCC [34].Zeng et al describe the comprehensive features of gastric cancer TME characteristics and provide new strategies for cancer treatment [35].A present study found that many elements of TME other than tumor epithelial cells influence the progression of HNSCC [36]. Another study highlights the favorable prognostic impact of an immune-inflamed TME in LUAD [37]. There is also studies analyzed the immune microenvironment of stage I LUAD and found that the high expression of IL-7R and the lower expression of IL-12Rβ2 were all independent factors of poor prognosis [38].Yue et al identified three TME-related DEGs signature which could be used to predict the prognosis of LUAD patients [39].Chen et al revealed the differentiated regulation of immuneresponse related genes between LUAD and LUSC [28].…”
Section: Discussionmentioning
confidence: 56%
“…In this study, we demonstrate that immune cell specific PTPN2 plays an important role in the development of human CRC. Using a large collective of tissue samples from CRC patients, we show that PTPN2 protein expression and activity was highly elevated in human CRC tissue, with a marked increase in immune cells, and that high Since in the majority of CRC patients, low immunogenicity of the tumors prevents response to immunotherapies (7,8,25,26), therapeutic approaches that promote the immunogenic potential provide a strong rationale for improving treatment success. Our data from primary and metastatic human CRC tissues indicate a strong correlation of local PTPN2 expression and reduced immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, more than 1.8 million patients were newly diagnosed with CRC and despite improved 5-year survival, the estimated number of CRC-related deaths accumulated to 881,000 (3)(4)(5)(6). Successful immunotherapeutic interventions in other solid cancers, such as melanoma and lung carcinoma have exploited their tumor microenvironment, which contains high numbers of immune cells, such as T-cells, natural killer (NK) cells and antigen-presenting cells (7,8). The majority of CRC, however, lack prominent immune infiltrates and only about 4% of all CRC cases respond to immunotherapies (2,9).…”
Section: Introductionmentioning
confidence: 99%